Development of Metallic Aluminium Foam Casting Using Calcium Carbonate Precursors for Side Impact Beam Application. (2018) - Sowmiya, S.; Nallanukala, Prasad; Anburaj, J.; Simhachalam, Bade
Abstract: This paper focuses on the development of Aluminium closed cell foams using Direct foaming method - ALPORAS process with calcium carbonate as foaming agent. The foaming of pure aluminium was carried out by varying the weight of calcium carbonate with different foaming temperatures and stirring duration. The presence of pores formed and also its distribution in the cast product was characterized by visual inspection. The morphology of pores in foamed aluminium was characterized by aided visual examination. From the characterization results, the optimum parameters were determined for foaming process. Tubes used for side impact beams should possess higher crashworthiness, which is improved by using foam fillings. In order to explore the total energy absorption, the tube with and without foam was numerically simulated using LS DYNA.